2018
DOI: 10.1021/acs.biochem.8b00425
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Functionally Important Aromatic Residue Interactions in the Extracellular Domain of the Glycine Receptor

Abstract: The extracellular domains (ECDs) of Cys-loop receptors contain many aromatic amino acids, but only relatively few have been well studied. Here we explore the roles of Tyr and Trp residues in the ECD of the glycine receptor and show that four such residues that have not been previously studied (Y24, Y58, W170, and Y197) contribute significantly to the function of the protein. The residues were studied by creating mutant receptors, characterizing them using two-electrode voltage clamp in Xenopus oocytes, and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Studies have indicated several possible routes by which M4 residues could affect channel function, and 2 of these have been more extensively investigated. The first is through direct interaction with the M1/M3 helices, a route which is supported by a range of studies demonstrating, in particular, the importance of aromatic interactions of M4 with M1/M3. ,, In addition, specific links for some residues have been identified, as in the case of the C418W mutation in the Torpedo nAChR, which couples energetically with residues in M1 to stabilize the open state, decreasing EC 50 . The second route involves the interaction of the tip of M4 with the Cys-loop.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have indicated several possible routes by which M4 residues could affect channel function, and 2 of these have been more extensively investigated. The first is through direct interaction with the M1/M3 helices, a route which is supported by a range of studies demonstrating, in particular, the importance of aromatic interactions of M4 with M1/M3. ,, In addition, specific links for some residues have been identified, as in the case of the C418W mutation in the Torpedo nAChR, which couples energetically with residues in M1 to stabilize the open state, decreasing EC 50 . The second route involves the interaction of the tip of M4 with the Cys-loop.…”
Section: Discussionmentioning
confidence: 94%
“…In the context of LGICs, this means that mutations in the ECD, including those at or near the subunit interface, tend to result in increased EC 50 values for ligands binding at the orthosteric binding site or more generally disrupt channel function. This has been observed for a variety of LGICs, such as GlyR α1, nAChR α7 and iGluRs (Braun et al, 2016; Iacobucci et al, 2021; Tang et al, 2018; Tang & Lummis, 2018; Weston et al, 2006). In fact, even mutational scans in the ECD of a close cousin of the P2X2R, the P2X1R, have established that the vast majority of mutations result in increased EC 50 values (Ennion et al, 2000; Roberts & Evans, 2004, 2006).…”
Section: Discussionmentioning
confidence: 59%
“…In the context of ligand‐gated ion channels, this means that mutations in the extracellular domain, including those at or near the subunit interface, tend to result in increased EC 50 values for ligands binding at the orthosteric binding site or more generally disrupt channel function. This has been observed for a variety of ligand‐gated ion channels, such as glycine receptor α1 subunit, nicotinic acetylcholine receptor α7 subunit and ionotropic glutamate receptors (Braun et al, 2016; Iacobucci et al, 2021; Tang et al, 2018; Tang & Lummis, 2018; Weston et al, 2006). In fact, even mutational scans in the extracellular domain of a close cousin of the P2X2 receptor, the P2X1 receptor, have established that the vast majority of mutations result in increased EC 50 values (Ennion et al, 2000; Roberts & Evans, 2004, 2006).…”
Section: Discussionmentioning
confidence: 79%